PERCEPTIONS OF PRIVATE SECURITY: A CASE STUDY OF STUDENTS FROM SERBIA AND NORTH MACEDONIA - Janković, Bojan D; Cvetković, Vladimir M; Ivanov, Aleksandar (NBP. Nauka, bezbednosti, policija, 2019)
In the last two decades of the 21st century, the significant development of the private security industry has taken place in Serbia and North Macedonia. However, the private security industry in these two countries did not reach professional standards as in other countries of the former Yugoslavia. The aim of this paper was to determine students’ perception of private security and its employees. The survey data were collected using an anonymous survey of 354 students (296 from Serbia and 58 from North Macedonia). In both countries, attitudes are heterogeneous, but a relatively small number of respondents have expressed a high level of perception of private security. The research has shown that gender, as one of demographic characteristics, has its role in shaping young people’s views on the private security, that is, the female population has more positive views about private security guards, their integrity, and the nature of the private security job. The findings offer policy-makers and private security companies the opportunity to develop new strategies to improve public attitudes towards private security.